Fifty modern thinkers on education : from Piaget to the present - Palmer, Joy, 1951-; Cooper, David E. (David Edward), 1942-; Bresler, Liora (Routledge key guides, 2001)
Looks at fifty of the twentieth century's most significant contributors to the debate on education. Each essay gives key biographical information, an outline of the individual's principal achievements and activities, an assessment of his or her impact and influence and a list of their major writings and suggested further reading.